Kajian Penanganan Sedimentasi Sungai Banjir Kanal Barat Kota Semarang (Study of Sedimentation Mitigation West Floodway Semarang City) - Prasetyo, Dani; Dermawan, Very; H., Andre Primantyo (Fakultas Teknik, Universitas Brawijaya, 2015)
For the flood control of Semarang City,one of part needed is sedimentation mitigation atthe West Floodway river. This study is carried out to predictdistribution patterns and sediment volumein the West Floodway. The simulation of existing conditions is the first step for determination of sediment transport model. The models will be used to predicting sedimentation until year 2019 and 2024 on the condition without and with sediment mitigation alternatives. Based on the existing condition simulation, the average of elevation increase in 2019 and 2024 respectively are 1,864 m and 2,210 m. The estimation of sediment volume in 2019 and 2024 respectively are 1.053.524 m³ and 1.223.693 m³. The results of sediment transport prediction with sediment pocket showing the lowest average elevation in 2019 and 2024 respectively are 1,379 m and 1,992 m.The smallest volume of sediment obtained by dredging with dredger in 2019 and 2024 respectively are 791.161 m³ and 1.099.685 m³. Based on cost estimation,the cost of dredging with dredger is the lowest, at a cost 32.267.637.478 IDR.Keyword: sedimentation, HEC-RAS, prediction, elevation, volume, cost